C10orf10/DEPP activates mitochondrial autophagy and maintains chondrocyte viability in the pathogenesis of osteoarthritis. Issue 2 (8th January 2022) - Kuwahara, Masanari; Akasaki, Yukio; Kurakazu, Ichiro; Sueishi, Takuya; Toya, Masakazu; Uchida, Taisuke; Tsutsui, Tomoaki; Hirose, Ryota; Tsushima, Hidetoshi; Teramura, Takeshi; Nakashima, Yasuharu
Abstract: Osteoarthritis (OA), the most prevalent joint disease, is characterized by the progressive loss of articular cartilage. Autophagy, a lysosomal degradation pathway, maintains cellular homeostasis, and autophagic dysfunction in chondrocytes is a hallmark of OA pathogenesis. However, the cause of autophagic dysfunction in OA chondrocytes remains incompletely understood. Recent studies have reported that decidual protein induced by progesterone (C10orf10/DEPP) positively regulates autophagic functions. In this study, we found that DEPP was involved in mitochondrial autophagic functions of chondrocytes, as well as in OA pathogenesis. DEPP expression decreased in human OA chondrocytes in the absence or presence of pro‐inflammatory cytokines, and was induced by starvation, hydrogen peroxide (H2 O2 ), and hypoxia (cobalt chloride). For functional studies, DEPP knockdown decreased autophagic flux induced by H2 O2, whereas DEPP overexpression increased autophagic flux and maintained cell viability following H2 O2 treatment. DEPP was downregulated by knockdown of forkhead box class O (FOXO) transcription factors and modulated the autophagic function regulated by FOXO3. In an OA mouse model by destabilization of the medial meniscus, DEPP‐knockout mice exacerbated the progression of cartilage degradation with TUNEL‐positive cells, and chondrocytes isolated from knockout mice were decreased autophagic flux and increased cell death following H2 O2 treatment. Subcellular fractionation analysis revealed that mitochondria‐located DEPP activated mitochondrial autophagy via BCL2 interacting protein 3. Taken together, our data demonstrate that DEPP is a major stress‐inducible gene involved in the activation of mitochondrial autophagy in chondrocytes, and maintains chondrocyte viability during OA pathogenesis. DEPP represents a potential therapeutic target for enhancing autophagy in patients with OA.